Asperger syndrome in the inclusive classroom : advice and strategies for teachers - Betts, Stacey W. (Stacey Waldman), 1964- (Jessica Kingsley Publishers, 2007)
A goldmine of practical strategies that will be of benefit to teachers with or without experience. This is an extremely readable book which is packed full of practical advice, strategies and opportunities for reflection on managing young people's lives at school, with down to earth text covering such areas as curriculum, transport, discipline, unstructured time and much more. The book enables an individual and whole school approach to facilitate inclusion with an emphasis on learning."--Elaine Colquhoun, President, NASEN. "Asperger Syndrome in the Inclusive Classroom: Advice and St